PENERAPAN SISTEM INFORMASI MANAJEMAN PADA UMKM KABUPATEN PESAWARAN MENGGUNAKAN METODE USE CASE POINT - Rudi Kurniawan; Muhammad Reza Romahdoni; Anas Khair Prikurnia (LP2M Institut Informatika Dan Bisnis Darmajaya, 2024)
SMEs in Indonesia, particularly in Pesawaran Regency, play a pivotal role in driving economic growth, job creation, and poverty alleviation. Despite their significance, these small and medium-sized enterprises face numerous challenges, including limited capital, restricted market access, poor financial management, human resource shortages, lack of differentiation and innovation, inadequate technology adoption, and complex regulatory hurdles. To address these issues, a Use Case Point analysis was conducted to evaluate the feasibility and scope of developing an Information Management System specifically tailored for SMEs in Pesawaran Regency. The analysis began by determining the Unadjusted Actor Weight and Unadjusted Use Case Weight to assess the system's complexity. Further, the Technical Complexity Factor and Environmental Factor were evaluated based on the system's requirements. Subsequent calculations involved determining the Productivity Factor, Effort Estimation, and Use Case Points. The findings of this research indicate that the development of the proposed Information Management System poses minimal risk, given the relatively low workload and small team size required. The project was estimated to have 63.8 Use Case Points with a Productivity Factor and Effort Estimation of 1,261 hours.